Manual development and efficacy of Mindful Living Group activities to promote trauma healing during the COVID-19 pandemic in China - Niu, Ya-Nan; Long, Di (Frontiers in Public Health, 2023)
Disasters can be traumatic with a profound and lasting impact on individuals. During the COVID-19 pandemic, our team developed the Mindful Living Group (MLG) activities manual based on Eastern body-mind wisdom and Western trauma healing theory to provide psychological assistance for trauma healing. In this study, we introduce a framework developed for the 10-session MLG activities manual, which consists of 3 core modules. Thirty-one participants living all over the country who had experienced traumatic stress resulting from the COVID-19 pandemic received the MLG intervention. This single-arm intervention study offered psychological assistance during the pandemic. The MLG intervention included 10 weekly 2-hour sessions held online. Participants completed the initial interview, pretest, posttest, and 1-month follow-up interviews. The effectiveness of the MLG activities manual was evaluated using psychological measures, including the Mindful Attention Awareness Scale, Self-Rating Depression Scale, Self-Rating Anxiety Scale, Posttraumatic Growth Inventory, Perceived Social Support Scale, and the General Self-Efficacy Scale. Compared with the pretest level, the posttest levels of depression (F = 42.78, p < .001, η2 = .59) and anxiety (F = 23.40, p < .001, η2 = .44) were significantly lower; and mindfulness (F = 12.98, p = .001, η2 = .30), posttraumatic growth (F = 27.06, p < .001, η2 = .48), general self-efficacy (F = 13.20, p = .001, η2 = .31), and perceived social support (F = 16.27, p < .001, η2 = .35) were significantly higher (ANOVA). Further correlation analysis revealed a significant negative relationship of mindfulness with both depression (r = –.43, p = .015) and anxiety (r = –.35, p = .053), and significant positive relationships of mindfulness with posttraumatic growth (r = .40, p = .025), general self-efficacy (r = .52, p = .003), and perceived social support (r = .40, p = .024). These preliminary findings are consistent with those of previous reports on mindfulness-based intervention outcomes in trauma treatment. The mechanisms underlying mindfulness promoting trauma healing are discussed based on both Eastern body-mind wisdom and Western theories of trauma healing. Clinical Trail Registration: ChiCTR2000034164